Condylar Hyperplasia. A Case Presentation - Yordany Boza Mejias; Bienvenido Mesa Reinaldo; Osmany Villa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Condylar hyperplasia should be carefully studied as one of the affectations of the temporomandibular. This condition is most common in women than in men and mostly in adulthood. As clinical characteristic it presents facial asymmetry. For the diagnosis of these cases, tests that range from simple radiographies to more complex studies such as computed tomography scans are necessary. Because of the rareness of this condition in our setting, we present the case report of a patient with condylar hyperplasia that was treated at the Maxillofacial Surgery Service of the Dr. Gustavo Aldereguía Lima General University Hospital in Cienfuegos.